Comparative assessment of knowledge, attitude, and practice toward self-medication among health and non-health students at Daffodil International University, Dhaka (2022–2023) - Md. Mizanur Rahman; Md. Jahir Alam; Ms Tamanna Khatun; Chaity Sutar; Shabnaz Akter; As-Ad Din Mahmood; Sher Mostafa Sadiq Khan (International Journal of Public Health Science (IJPHS), 2026)
Self-medication, a popular self-care practice, is common throughout the world and is responsible for serious health complications. The present investigation assessed the knowledge, attitudes, and practices of self-medication among healthcare and non-healthcare students at Daffodil International University, Savar, Dhaka, Bangladesh. A cross-sectional survey of 240 students from the Pharmacy and Environmental Science Departments, ages 19 to 24, was carried out between October 2022 and January 2023. Socio-demographics, knowledge, attitudes, information sources, common medications, and diseases treated were all covered in the pre-tested questionnaire used to gather data. SPSS v16.0 with correlations and descriptive statistics was used for the analysis. Among 240 participants, 50.8% were health science students and 49.2% were non-health science students; 45.8% were male, and 54.2% were female. Most (74.2%, p < 0.01) were aged 21-22 years, mainly in the 4th year (43.3%, p < 0.001). Knowledge analysis showed 37.5% knew over-the-counter (OTC) drugs (p < 0.001) and 55% supported self-medication for minor illness. Common conditions treated were headache (49.2%), fever (23.3%), and cold (16.7%). Painkillers were the most used drugs (39.2%), with family members as the main source of advice (50%). Knowledge had a significant correlation with health science students (p < 0.001). Attitudes revealed 70% used self-medication in the last 6 months; 67.5% discouraged peers, 55.8% reused prescriptions, 73.3% read leaflets, and 61.2% consulted doctors for adverse effects. Previous experiences (74.2%) were the main reason for self-medication. Self-medication is widespread among university students. Health science students demonstrated better knowledge and awareness against self medication while contrasted to non-healthcare students. Awareness programs are needed for all groups.